Auditory observation of infant-directed speech by mothers: experience-dependent interaction between language and emotion in the basal ganglia - Matsuda, Yoshi-Taka; Ueno, Kenichi; Cheng, Kang; Konishi, Yukuo; Mazuka, Reiko; Okanoya, Kazuo (Frontiers in Human Neuroscience, 2014)
Adults address infants with a special speech register known as infant-directed speech (IDS), which conveys both linguistic and emotional information through its characteristic lexicon and exaggerated prosody (e.g., higher pitched, slower, and hyperarticulated). Although caregivers are known to regulate the usage of IDS (linguistic and emotional components) depending on their child’s development, the underlying neural substrates of this flexible modification are largely unknown. Here, using an auditory observation method and functional magnetic resonance imaging (fMRI) of four different groups of females, we revealed the experience-dependent influence of the emotional component on linguistic processing in the right caudate nucleus when mothers process IDS: (1) non-mothers, who do not use IDS regularly, showed no significant difference between IDS and adult-directed speech (ADS); (2) mothers with preverbal infants, who primarily use the emotional component of IDS, showed the main effect of the emotional component of IDS; (3) mothers with toddlers at the two-word stage, who use both linguistic and emotional components of IDS, showed an interaction between the linguistic and emotional components of IDS; and (4) mothers with school-age children, who use ADS rather than IDS toward their children, showed a tendency toward the main effect of ADS. The task that was most comparable to the naturalistic categories of IDS (i.e., explicit-language and implicit-emotion processing) recruited the right caudate nucleus, but it was not recruited in the control, less naturalistic condition (explicit-emotion and implicit-language processing). Our results indicate that the right caudate nucleus processes experience- and task-dependent interactions between language and emotion in mothers’ IDS.